MBRS-45. TWIST1 AND ABCB1 ARE FUNCTIONAL DETERMINANTS OF METASTASIS IN MEDULLOBLASTOMA. (4th December 2020) - Cardall, Alice; Linke, Franziska; Kerr, Ian; Coyle, Beth
Abstract: Paediatric medulloblastomas (MB) are frequently metastatic, resulting in a poor prognosis for the patient. Of the four MB subgroups, group 3 patients present with the highest rates of metastasis and worst outcomes. The mechanisms behind the metastatic process are poorly understood, limiting our ability to develop novel therapeutic treatments. We hypothesised that the epithelial-mesenchymal transition (EMT) transcription factor TWIST1 and the multidrug efflux pump ABCB1 (ATP-binding cassette subfamily B member 1) synergistically drive MB metastasis. TWIST1 protein expression was analysed in patient tissue microarrays by immunohistochemistry. High TWIST1 expression was associated with metastatic patients (p=0.041). Physical and functional interactions between TWIST1 and ABCB1 were investigated using chromatin immunoprecipitation (ChIP) and a 3D migration and invasion model. ChIP analysis confirmed TWIST1 binding to the ABCB1 promoter in SHH (ONS-76) and group 3 (D283MED and HD-MB03) metastatic cell lines. TWIST1 and ABCB1 were inhibited in HDMB03 cells with harmine and vardenafil respectively, resulting in attenuated cell migration in the 3D model. Western blot and qRT-PCR analysis of harmine treated cells confirmed a reduction in ABCB1 protein and gene expression. Overall our data reveals TWIST1 and ABCB1 to be key targets for MB metastatic disease. Using bioinformatics analysis and ChIP sequencing, additional TWIST1 downstream targets are now being identified and compared across the metastatic cell lines (ONS-76, D283MED and HD-MB03). This data will provide a deeper insight into the pathways associated with MB metastases, enabling personalised treatment approaches for patients with metastatic disease.